You are on page 1of 1

Emma McVicar

EECS 212, HW 16

1. Use induction on n to prove that gcd(a nb, b) = gcd(a, b) for all positive integers a
and b and all n 1. (Hint: in the base case, show that gcd(a nb, b) gcd(a, b) and
gcd(a, b) gcd(a b, b).)
BASE CASE: n=1
gcd(a - b, b) = gcd(a, b)
By definition, gcd(a, b) must divide integers a and b. This means that there exist
some integers j and k such that (k)gcd(a, b) = a and (j)gcd(a, b) = b. In turn, this means
that there exists some integer i such that (i)gcd(a, b) = a - b. Because gdc(a, b) divides a
and b, it must also divide a - b. Therefore, gcd(a, b) = gcd(a - b, b).
INDUCTIVE STEP:
gcd(a-(n+1)b, b) = gcd(a, b)
We know that gcd(a, b) divides bn, meaning gcd(a, b) must also divide b(n+1).
Using the same logic as the base case, we can prove that because gcd(a, b) divides both a
and b, it must also divide any integer x such that x = sa + tb, for some integers s and t.
Therefore, for every integer n greater than or equal to zero, gcd(a-nb, b) = gcd(a, b).

2. Let Fn represent the Fibonacci numbers, defined by the recurrence Fn = Fn1 + Fn2, F0
= 0, and F1 = 1. Prove that Fn and Fn+1 are coprime for all n 1. (Hint: use the result
of the previous problem.)
Prove that gcd(Fn, Fn+1) = 1 for all integers n greater than or equal to 1. For the
base case, gcd(0, 1), we know this is true. For Fn and Fn+1, we can determine:
Fn = Fn-1 + Fn-2
and

Fn+1 = Fn + Fn-1 = (Fn-1 + Fn-2) + Fn-1 = 2Fn-1 + Fn-2

which means that gcd(Fn, Fn+1) can be rewritten as gcd(Fn-1 + Fn-2, 2Fn-1 + Fn-2), and
is Fn-1 = a and Fn-2 = b, gcd(a + b, 2a + b). Because we know that gcd(F0, F1) is 1, and
that gcd(Fn, Fn+1) is a linear combination of F0 and F1, this means that gcd(Fn, Fn+1)
must be equal to gcd(F0, F1), which is 1. Because gcd(Fn, Fn+1) = 1, this means that
they are coprime.

You might also like